(untitled) (Medicine Today, 2020)
Introduction: Retinal diseases especially those due to diabetes and AMD are coming up as important causes of blindness and visual impairment. Our study is to evaluate the frequency and pattern of retinal diseases in ophthalmic outpatient department of a district hospital in Bangladesh. Materials and Methods: A total number of 173 referred new retina cases were reviewed at outpatient department of the 250 beded General Hospital, Jamalpur, Bangladesh, between February 2017 and November 2017. Data was analyzed according to age, sex and clinical diagnoses and detailed fundus evaluation done with binocular indirect ophthalmoscope and slit lamp using 20D and 90D lenses respectively. Results: Out of 7164 new patients,of whom 173 patients were (2.42%) presented with retinal diseases.139 patients were reviewed and followed up. Male: female ratio was 1.24:1. Out of 139 patients 77 (55.4%) were males and 62 (44.6%) females with a peak age group of 41-50 years. Diabeticrelated retinal conditions were 36 cases (25.9%), the most common cause.16 (44.44% of total DR) patients had CSME and 5(14.9%) had ADED. Diabetic retinopathy 36 cases (25.9%), Chorioretinitis 20 cases (14.4%), ARMD 11 cases (7.9%), and Optic atrophy 10 cases (7.2%). Conclusion: Retinal diseases remain an important cause of visual morbidity. There is increasing incidence of retinal blindness especially diabetic retinopathy in Bangladesh. The impression based on hospital practice is that the problem is increasing. This entails the necessity for accessible comprehensive eye care services, establishment of human resources, screening and awareness of the disease and affordable eye health policy. Medicine Today 2020 Vol.32(1): 1-4